Isolation by phenology synergizes isolation by distance across a continuous landscape. Issue 3 (7th August 2019) - Peters, Madeline A. E.; Weis, Arthur E.
Summary: Pollen is generally dispersed over short distances, which promotes population genetic structure across continuous two‐dimensional space. Quantitative genetic variance in flowering time structures mating pools in the temporal dimension, at least with respect to the phenology loci. We asked if these two phenomena, isolation by distance (IBD) and isolation by phenology (IBP), synergistically promote genetic structure. We constructed an individual‐based model that tracked genotype frequencies at flowering time and neutral loci across a uniform landscape, over multiple generations, under four mating schemes: panmixia, IBD only, IBP only, and IBP × IBD. IBD × IBP divided the population into spatial clusters of early‐, mid‐, and late‐flowering genotypes and strongly increased its quantitative genetic variance. Flowering time did not cluster under IBP, but its genetic variance increased moderately. IBD induced mild spatial structure in a nonassortative reference trait but did not change its variance. Importantly, the spatial correlation of genotypes at neutral loci was twice as strong under IBD × IBP compared with IBD alone. IBD × IBP also drew neutral loci into gametic disequilibrium with flowering time loci, structuring them temporally. Temporal and spatial mating pool structure promotes local differentiation. This trend would facilitate adaptation on small spatial scales.